1995
DOI: 10.1002/gps.930100509
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of hypercortisolaemia to the cognitive decline of geriatric depression

Abstract: SUMMARYCognitive impairment in depression is well recognized but poorly understood. A subset of depressed patients exhibit a syndrome of severe neuropsychological deficits which may be partially reversible upon episode resolution. This has been called depressive pseudodementia, the dementia syndrome of depression and depression induced cognitive impairment. The epidemiology, clinical features, natural history and prognosis of this condition support the notion of an underlying organic aetiology. The most plausi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…It is now well established that depressive symptoms are often accompanied with, caused by or lead to other cognitive function dependent mental health problems [1,14,15,19,33,39]. Currently, however, no consistent or successful therapeutic strategies to combat depression related cognitive impairments (DRCI) or cognitive decline of geriatric depression are available [25,26]. Confirmation of our experimental observations made with the Hypericum extract by properly controlled dose-finding studies in patients with dementia therefore seems warranted.…”
Section: Discussionmentioning
confidence: 59%
“…It is now well established that depressive symptoms are often accompanied with, caused by or lead to other cognitive function dependent mental health problems [1,14,15,19,33,39]. Currently, however, no consistent or successful therapeutic strategies to combat depression related cognitive impairments (DRCI) or cognitive decline of geriatric depression are available [25,26]. Confirmation of our experimental observations made with the Hypericum extract by properly controlled dose-finding studies in patients with dementia therefore seems warranted.…”
Section: Discussionmentioning
confidence: 59%
“…It is thus well established that approximately half of depressed patients have hypothalamicpituitary-adrenal (HPA) axis hyperactivity (11,67,68). This abnormality could implicate hippocampal dysfunction because of its inhibitory influence on the HPA axis (69)(70)(71).…”
Section: What Is the Mechanism Behind The Decreased Hippocampal Volume?mentioning
confidence: 99%
“…It is thus well established that approxi mately half of depressed patients have hypothalamic pituitary-adrenal (HPA) axis hyperactivity (11,67,68). This abnormality could implicate hippocampal dysfunction because of its inhibitory influence on the HPA axis (69)(70)(71). In a PET study of relatively acutely depressed patients, we found markedly increased blood flow to the hippocampus (12), whereas others have found decreased activity in the parahippocampal area in a study of patients with treat ment-resistant depression with a very long depression his tory (72).…”
Section: What Is the Mechanism Behind The Decreased Hippocampal Volume?mentioning
confidence: 99%